KONSEP PERUBAHAN DALAM HUKUM ISLAM - Y. Sonafist (INTELIGENSIA MEDIA, 2023)
The concept of legal change brought about by Islamic law is a reflection of the purpose and nature of Islamic law which aims to create a stable life in the world that is in accordance with God's intention as the maker of shari'ah. The purpose and essence of Islamic law consists of four aspects, namely; realizing the benefit of humans in this world and the hereafter, the realization of the benefit of Islamic law must be understood so that it is in accordance with human nature, after obtaining a correct understanding, Islamic law must be implemented by Muslims, so that it can provide legal protection and tranquility for Muslims even against non-Muslims though. Islamic law is not just a static norm that prioritizes certainty and order, but also norms that must be able to dynamically think and manipulate people's behavior in realizing their goals. In order to develop the thoughts and studies of Islamic law in the life of society in the future, it is time for Islamic law experts to consider the studies and thoughts of Islamic law within the framework of sociology and social history approaches.